VISUALIZING THE INVISIBLE: SKY PROTESTS AND CONTESTED LANDSCAPES OF LABOR IN SOUTH KOREA, 1990-2020 - (:unkn) unknown (My University, 2024)
This dissertation examines the emerging social phenomenon of sky protests in South Korea from 1990 to 2020. Sky protests exhibit different tactics compared to conventional labor protests in South Korea which heavily relied on labor militancy in the 1970s and 80s. Sky protesters display their bodies in high altitude spaces to visualize their existence, thus drawing empathy from their opponents, mass media, and citizens. While sky protests became pervasive in South Korea after 2000, they remain undertheorized and poorly understood. Existing literature focuses on how larger structures weaken workers’ power to resist unfair treatment. However, such an approach often ignores how sky protests help Korean workers confront their opponents. What distinguishes this dissertation from existing ones is a focus on how Korean workers actively employed space and spatial practices as a means of resistance to the influence of neoliberal repercussions. To make sense of sky protests, I borrow a theoretical lens from a series of works on ‘insurgent placemaking’ while also situating the issue within the context of South Korea. In this research, I consider space and spatial practices to be at the center of discussion, which is often ignored in research on social movements. Each chapter is organized by tracing the trajectory of staging sky protests: choosing a place of protest, sustaining political and daily activities within lofty heights and inhospitable environments, and building solidarity with diverse groups. Each chapter connects to public space discourse, everyday life, and spatial solidarity. I suggest that sky protesters’ had an attitudinal change toward their opponents which led to a diversification of places for staging protests. They no longer relied on aggressive or violent means but attempted to elicit empathy from their opponents to solve their issues. This implies that the attitudinal changes of Korean workers were spatially reflected through the diversification of protest places. In addition, I offer that incongruence between action and place played a crucial role in attracting public and mass media attention. This means that everyday activities served as a means of resistance during sky protests. Furthermore, sky protests exemplify that everyday built environments can play an essential role in remembering and forgetting the past and creating spatial solidarity between protesters and uninvolved citizens. Based on these key findings, this dissertation contributes to exemplifying insurgent placemaking. Particularly, I focus on the spatial and ephemeral qualities of resistance spaces, which often elude the critical eyes of scholars who examine buildings and cultures. In addition, this dissertation offers that sky protests are not merely a result of distorted larger socioeconomic systems influenced by neoliberalism. In contrast, they have become helpful for protesters in confronting their opponents, and the increasing number of sky protests since 2000 verifies it. Also, I suggest that space and spatial practice are principal elements in figuring out social movements. While each protester’s goals varied depending on the situation, their actions resulted in the temporal occupation of a high place. In other words, those engaging in sky protest partake in a creative form of resistance, which is also generative, by remaking space itself as both a tool and a platform to challenge social and political barriers.
Keywords: built environment; everyday; labor; public space; sky protest; solidarity